2000
DOI: 10.2307/3236773
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of plant life forms along an altitudinal gradient in the semi‐arid valley of Zapotitlán, Mexico

Abstract: Abstract. Plant life‐form abundance along a 600 m altitudinal gradient (1600–2200 m a.s.l.) in the semi‐arid valley of Zapotitlán, México was correlated with soil characteristics and climatic variables. One mixed soil sample was taken and analysed for each of six elevations, temperature was estimated using a terrestrial thermal gradient, and precipitation using a linear regression between total annual precipitation and the elevation of the weather stations in the valley. Rosettes, microphanerophytes, therophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
1
8

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 19 publications
1
50
1
8
Order By: Relevance
“…En general, se ha sugerido una correlación positiva siempre y cuando las especies tengan una historia evolutiva común en suelos de pH alto (Pärtel, 2002), lo que podría ser el caso de este trabajo. Para el Valle del Mezquital se reportaron valores de pH entre 7.2 y 7.3 (Montaño-Árias et al, 2006) y para el semidesierto de Tehuacán-Cuicatlán de 7.3 a 8.4 (Pavón, Hernández-Trejo, & Rico-Gray, 2000), mientras que en este estudio encontramos sitios con pH ligeramente ácidos de 5.8. Desconocemos si esto es una condición natural de los sitios o es derivado de actividades humanas; por ello es necesario realizar estudios para una evaluación apropiada.…”
Section: Resultsunclassified
“…En general, se ha sugerido una correlación positiva siempre y cuando las especies tengan una historia evolutiva común en suelos de pH alto (Pärtel, 2002), lo que podría ser el caso de este trabajo. Para el Valle del Mezquital se reportaron valores de pH entre 7.2 y 7.3 (Montaño-Árias et al, 2006) y para el semidesierto de Tehuacán-Cuicatlán de 7.3 a 8.4 (Pavón, Hernández-Trejo, & Rico-Gray, 2000), mientras que en este estudio encontramos sitios con pH ligeramente ácidos de 5.8. Desconocemos si esto es una condición natural de los sitios o es derivado de actividades humanas; por ello es necesario realizar estudios para una evaluación apropiada.…”
Section: Resultsunclassified
“…The relationship between the occurrence of different life forms, altitude and other environmental variables is well-known (Campbell & Werger 1988;Floret et al 1990;Montana & Valientebanuet 1998;Kessler 2000;Pavón et al 2000;Noy-Meir & Oron 2001;Klimeš 2003;Odland 2009). Hemicryptophytes have been found to be more frequent at higher altitudes in many mountain systems (Raunkiaer 1934;Wang et al 2002;Klimeš 2003;Noroozi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Kharkwal et al (2005) have also suggested that altitude and climatic conditions such as temperature and rainfall are the determinants of species richness. The life-forms diversity usually decreases with increasing altitudes and one or two life-form remains at extreme altitudes (Pavon et al 2000;Sharma et al 2009). Austin et al (1996), have analyzed association between of species richness, climate, slope and soil nutrient status.…”
Section: Discussionmentioning
confidence: 99%